Penerapan Sistem Tata Kerja Maintenance dengan Peninjauan Ulang Equipment Criticality Assessment (ECA), Failure Mode Effect Criticality Assessment (FMECA), dan Reliability Centered Maintenance (RCM) pada Sebuah Perusahaan Minyak dan Gas Bumi - Neni Tri Widiarti; Adithya Sudiarno; Idham Chalid (Lembaga Yasin AlSys, 2025)
This study examines the effectiveness of implementing the new Maintenance Work System (Sistem Tata Kerja or STK), enforced since 1 November 2024, in an oil and gas company, with a specific focus on the alignment between equipment criticality assessment outcomes and the revised STK requirements. The core issue lies in the potential shift in asset maintenance priorities and strategies due to misclassification of critical equipment, which may compromise operational reliability. The objective of this research is to revalidate the implementation of Equipment Criticality Assessment (ECA), Failure Mode Effect and Criticality Analysis (FMECA), and Reliability Centered Maintenance (RCM) to ensure they are applied more effectively and efficiently in accordance with international standards—IEC 60300-3-11, IEC 60812, and ISO 14224. The methodology includes document analysis of relevant standards, literature review, and criticality assessment of 182 equipment units using the Reliability Block Diagram (RBD) approach and SAP-based classification systems. The results show that turbomachinery, particularly Gas Turbine Compressors (GTC), remain classified as Production Critical Equipment (PCE), while the glycol system, auxiliary compressors, and gas metering units have been reclassified as secondary or supporting assets. The study recommends strengthening the technical competencies of the maintenance team, applying logic decision tree methodologies in the analytical process, and integrating evaluation outcomes into work scheduling policies and spare parts management. These findings offer practical contributions to the optimization of reliability-based maintenance systems and support more precise technical decision-making in the governance of strategic assets within the oil and gas sector.